The origins of rent control: From ancient Rome to Paris commune - Konstantin Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Urban areas are confronted with a chronic shortage of housing, especially in the low-rent segment. This precarious situation is further exacerbated by major challenges, like the destruction of housing by wars and natural catastrophes, rapid increase of demand, or a pandemic cutting incomes. In response, the authorities take advantage of rent control that slows down rent increases or even freezes rents. The hope is to guarantee the affordability of rental housing at least in the short run, until supply can expand and satisfy the demand for housing. Rent control became ubiquitous and has been used at a large scale since World War I. However, its roots lie in a far more remote past, the first documented examples stemming from the Ancient Rome. Despite social and technological differences between then and now, the solutions found more than 2000 years ago bear a striking similarity with modern policies. Rapidly rising housing costs, the COVID-19 pandemic, and the Ukrainian war pushed rent control back to the top of the political agenda. Therefore, diving into its origins can be a very instructive endeavor from the viewpoint of the current socioeconomic policy.
Keywords: 330